The Influence of Smart Technology Experience on Satisfaction Mediated by Generation Z Loyalty in Bali's Tourism and Hospitality Industry (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2026)
This study examines how Smart Technology Experience shapes Generation Z's satisfaction and loyalty to the tourism and hospitality industry in Bali, given the acceleration of digital transformation of services and the high expectations of young tourists for technology-based experiences. This study uses a quantitative approach with an explanatory design through a survey of Generation Z respondents who have experience using smart technology-based tourism and hospitality services in Bali. Data were analyzed using Partial Least Squares–Structural Equation Modeling to test the direct relationship between variables as well as the mediating role of satisfaction. The results of the analysis show that Smart Technology Experience has a positive effect on satisfaction, and satisfaction has a positive effect on loyalty. Smart Technology Experience also has a direct effect on loyalty, so that Generation Z's loyalty is not only formed through satisfaction evaluations, but also through the value of technology experiences that are directly felt. The mediation test indicates that satisfaction mediates the relationship between Smart Technology Experience and loyalty partially. These findings underscore the importance of managing consistent and relevant technology experiences to strengthen satisfaction while building Generation Z loyalty in the context of Bali destinations.